Discussion of "the evolution of boosting algorithms" and "extending statistical boosting" - Bühlmann, P; Gertheiss, J; Hieke, S; Kneib, T; Ma, S; Schumacher, M; Tutz, G; Wang, C-Y; Wang, Z; Ziegler, A (Methods of information in medicine, 2014)
This article is part of a For-Discussion-Section of Methods of Information in Medicine about the papers "The Evolution of Boosting Algorithms - From Machine Learning to Statistical Modelling" and "Extending Statistical Boosting - An Overview of Recent Methodological Developments", written by Andreas Mayr and co-authors. It is introduced by an editorial. This article contains the combined commentaries invited to independently comment on the Mayr et al. papers. In subsequent issues the discussion can continue through letters to the editor.